Decline of Neuropsychological Abilities in a Large Sample of Patients with Multiple Sclerosis: A Two-Year Longitudinal Study - Borghi, Martina; Carletto, Sara; Ostacoli, Luca; Scavelli, Francesco; Pia, Lorenzo; Pagani, Marco; Bertolotto, Antonio; Malucchi, Simona; Signori, Alessio; Cavallo, Marco (Frontiers in Human Neuroscience, 2016)
Objective: In this longitudinal study we monitored two large groups of MS patients and healthy controls for two years, with the aim of comparing their neuropsychological profile over time. Method: 322 patients with MS and 303 healthy controls were administered the Brief Repeatable Battery of Neuropsychological tests (BRB-N); neuropsychiatric measures were also administered. Two follow-ups were scheduled at one and two years, respectively. Results: A linear mixed model (LMM) with random intercept was run by considering participants’ performance on each test of the BRB-N at the three assessment points (baseline and follow-ups) as the within-subjects variable, and group (patients and controls) as the between-subjects factor. The interaction term was statistically significant for the tests: SDMT (p = 0.044), PASAT-2 (p = 0.011) and WLG (p < 0.001), whereas for the PASAT-3 approached statistical significance (p = 0.05). In addition, a LMM with random intercept was also run by identifying three groups (controls, RR-MS, and prog-MS). The interaction term was statistically significant for: PASAT-3 (p = 0.017), PASAT-2 (p = 0.0026), and WLG (p = 0.0022). Conclusions: Our results corroborate on a very large scale evidence that the abilities tapped by the tasks SDMT, PASAT and WLG are particularly sensitive to MS, and further extend this issue by showing that these abilities are likely to be more sensitive than others to the progression of the disease, as compared to healthy controls.